1989
DOI: 10.1021/j100339a067
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of the precursor of spreading drops of siloxane oil on glass, fused silica, and mica

Abstract: J. Phys. Chem.of Figure 12 corresponds to gzz, g, , , and gYy, respectively, in the above equations. (Note that in circumstances that the 0, ground state becomes a12b22a12a~b12; 2Bl, then one has to reverse the x and y axis designation.) For the case of the 2A2 ground state one calculates 6 = 1.23 eV. The larger crystal field parameter 6 = 1.23 eV for [ C~~C r ] + o~-/ N a~~-y compared to 6 = 0.424 eV for 02-/NaM-Y is n o t e~o r t h y .~~,~' ,~~ For matrix-isolated alkali-metal superoxide M 0 2 species, 6 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 0 publications
0
55
0
Order By: Relevance
“…The first reported observation of an 'invisible' film spreading ahead of the edge of a macroscopic drop stems from the pioneering work by (Hardy 1919 and1936), Hardy was unable to detect its presence directly at that time. Numerous studies have subsequently confirmed the existence of precursor films using ellipsometry Beaglehole (1989); Bascom et al (1964), interference microscopy patterns Bascom et al (1964), and polarized reflection microscopy (Ausserre et al 1986). Simultaneous observations of the moving droplet and of the fringe pattern by the laser ellipsometry (Ueno and Watanabe 2005) reveal the existence of the precursor film, which is ahead the moving contact line and traveled with varying its profile.…”
Section: Precursor Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…The first reported observation of an 'invisible' film spreading ahead of the edge of a macroscopic drop stems from the pioneering work by (Hardy 1919 and1936), Hardy was unable to detect its presence directly at that time. Numerous studies have subsequently confirmed the existence of precursor films using ellipsometry Beaglehole (1989); Bascom et al (1964), interference microscopy patterns Bascom et al (1964), and polarized reflection microscopy (Ausserre et al 1986). Simultaneous observations of the moving droplet and of the fringe pattern by the laser ellipsometry (Ueno and Watanabe 2005) reveal the existence of the precursor film, which is ahead the moving contact line and traveled with varying its profile.…”
Section: Precursor Filmmentioning
confidence: 99%
“…The typical thickness of the precursor film moving in front of macroscopic body of fluid is in the range of 500-3000 Å (Bascom et al 1964;Beaglehole 1989). For a fixed volume of water droplet, according to Tanner's laws (Tanner 1979), the spreading of the macroscopic part of the droplet is rather slow; it would take a very long time to completely spread a macroscopic drop (Voinov 1976;Tanner 1979).…”
Section: Precursor Filmmentioning
confidence: 99%
“…Systematic deviations of the expected spreading behavior of silicon oils were detected and found to be dependent on the chemical compositions of glass surfaces. [11] In the literature, both accelerations [12,13] and delaying [14] of the macroscopic spreading process were reported. Recently, Shanahan and Carre [15] found an anomalous spreading behavior of tricresyl phosphate (TCP) on glass and polymer surfaces in comparison with silicon oil and poly(dimethylsiloxane).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This force pulls out of the drop a film whose thickness results from a balance between the large capillary term and large disjoining pressure [1], and the extent of the film can be macroscopic. The spreading and thin-film dynamics of the precursor film have been the subject of a number of theoretical [2,3] and experimental [4][5][6][7][8][9][10] papers. The profile of the macroscopic droplet is measured using interference microscopy [11] but thickness of the precursor film is experimentally measured using ellipsometry [5,8].…”
Section: Introductionmentioning
confidence: 99%